The Influence of Corporate Governance Structure on Executive Compensation: Evidence from China - Yang, Hang (2018)
The aim of this dissertation is to provide an insightful understanding of executive compensation and its determinants in Chinese listed firms. It tests whether company performance is positively associated with executive pay. Additionally, it explores the impacts of corporate governance structure on managerial pay in China.